Advertisement calls of seven species of Sarawak frogs from the family Megophryidae - Muhammad Fadzil, Amram; Ramlah, Zainudin (UMK Publisher, 2025)
The vocalization patterns of frogs in the family Megophryidae from Sarawak, Malaysia, play a crucial role in their behavioral ecology. This study aims to document and analyze the advertisement calls of seven Megophryidae species across diverse habitats in Sarawak. Using field recordings and acoustic analysis, distinct call characteristics, including frequency, duration, and temporal patterns, were identified. Advertisement calls were recorded and analyzed using SoundRuler Acoustic Analysis (ver. 0.9.6.0) and Praat Acoustic Software, allowing for species differentiation based on call parameters. The results revealed species-specific variations in vocalization, with pulse note count, note repetition rate, and dominant frequency emerging as the most distinguishing features. Leptobrachium ingeri exhibited the highest number of pulsed notes per call, while Leptobrachella gracilis demonstrated the highest note repetition rate, and Leptobrachella mjobergi produced the highest dominant frequency. These findings enhance our understanding of species-specific vocalizations and their ecological significance, particularly in mate selection, territorial defense, and environmental adaptation. This study underscores the importance of acoustic monitoring in biodiversity conservation and provides a foundation for future research on amphibian communication in tropical ecosystems.